2018
DOI: 10.1515/sspjce-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Select geotechnical properties of a lime stabilized expansive soil amended with bagasse ash and coconut shell powder

Abstract: Lime stabilization has been and still is one of the most preferred methods for stabilization of expansive soils. However, in the recent times, utilization of solid waste materials in soil stabilization has gained prominence as an effective means to manage wastes generated from various sources. In this work, an attempt has been made to utilize waste materials from two sources as auxiliary additives to lime in the stabilization of an expansive soil. Bagasse ash (BA), a waste by-product from the sugar industry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This occurs through speeding up the stabilizing process by quickening the breakdown of the structure plus the creation of new reaction products [1,15,42]. The microstructural analysis as reported previously also confirms this role of SCBA [15,31,43]. In these findings, this SCBA stabilization process enhancement was also indicated by a reduction of unreacted soil zones.…”
Section: California Bearing Ratiosupporting
confidence: 83%
See 3 more Smart Citations
“…This occurs through speeding up the stabilizing process by quickening the breakdown of the structure plus the creation of new reaction products [1,15,42]. The microstructural analysis as reported previously also confirms this role of SCBA [15,31,43]. In these findings, this SCBA stabilization process enhancement was also indicated by a reduction of unreacted soil zones.…”
Section: California Bearing Ratiosupporting
confidence: 83%
“…The chemical analysis showed that the SCBA contained very high components of amorphous silica at 63.59% and alumina at 5.66%, which are needed to facilitate the chemical reaction with calcium oxide from hydrated lime to facilitate a pozzolanic reaction, as identified by [33]. In line with that, hydrated lime also contains the essential ingredient CaO, which is highly needed to produce hydrates in the pozzolanic reaction [31].…”
Section: Sugarcane Bagasse Ash (Scba)mentioning
confidence: 69%
See 2 more Smart Citations
“…However, given that the chemical contents do vary greatly due to difference in environmental conditions. For example, a combination of the three elements contributing to the pozzolanic reaction of Fe2O; Al2O3, and SiO2 can vary so widely, Srinivasan and Sathiya (2010) 90.5% for the three; 95.29% in Loganayagan et al, (2020); 73% in Venkatesh and Pradeepa (2019); 70.48% Anupam et al (2013) and as low as 40.66% (James and Pandian (2018), and 71.22% (Barasa et al, (2015) done in Kenya. Therefore, since there a paucity of literature in the East African region, more studies are still needed.…”
Section: Introductionmentioning
confidence: 99%